2004
DOI: 10.1017/s0014479704002029
|View full text |Cite
|
Sign up to set email alerts
|

Participatory on-Farm Conservation Tillage Trial in the Ethiopian Highland Vertisols: The Impact of Potassium Application on Crop Yields

Abstract: The two years on-farm tillage research during the 1999 and 2000 cropping seasons in an Ethiopian highland Vertisol area demonstrated the importance of adapting cultural practices into participatory trials. The minimum tillage package could be an effective intervention for soil conservation due to the early-vegetative cover of the soil. Based on farmers' application of ash on Vertisols at Chefe Donsa, the incorporation of 50 kg ha −1 of potassium sulphate (K 2 SO 4 ) in the on-farm trial significantly increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 8 publications
4
23
0
Order By: Relevance
“…The deficient tissue K content was not predicted by the soil exchangeable K test. Similarly, response to K has been observed on Ethiopian Vertisols with high amount of ammonium acetate extractable K [78]. This was further supported by the findings of Suba and Srivastava [79], who reported that Vertisols with high exchangeable and non-exchangeable K showed a response to applied K, though the response was different depending on the type of plant.…”
Section: Wheat Nutrient Statussupporting
confidence: 78%
“…The deficient tissue K content was not predicted by the soil exchangeable K test. Similarly, response to K has been observed on Ethiopian Vertisols with high amount of ammonium acetate extractable K [78]. This was further supported by the findings of Suba and Srivastava [79], who reported that Vertisols with high exchangeable and non-exchangeable K showed a response to applied K, though the response was different depending on the type of plant.…”
Section: Wheat Nutrient Statussupporting
confidence: 78%
“…Soil erosion and limited use of external nutrient inputs severely exhausted plant nutrients from the soil and declined soil fertility because of high nutrient losses, and are the major factors limiting crop production in rainfed and irrigated farms of the different agro-ecological zones of Tigray (Virgo and Munro, 1978;Mitiku, 1996). Nutrient mining due to sub optimal fertilizer use coupled with unblended fertilizer use favored the emergence of multi nutrient deficiency in Ethiopian soils (Astatke et al, 2004;Wassie et al, 2010;Wassie and Shiferaw, 2011) and resulted in stagnant crop production.…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient mining due to sub optimal fertilizer use coupled with agronomical unblended fertilizer uses have favored the emergence of multi nutrient deficiency in Ethiopian soils [4,5], which in part explain fertilizer factor productivity decline and stagnant crop productivity conditions encountered despite continued use the blanket recommendation. Soil fertility depletion is the major constraint to sustainable agricultural production in Tigray [6].…”
Section: Introductionmentioning
confidence: 99%